How to build successful business relationships - Kay, Frances 1949- (London, United Kingdom The Institution of Engineering and Technology, 2009)
The book has 10 chapters. The following topics are dealt with: business relationships; people networking; new business challenges; business communication; people management; team working; referrals; personnel rewards; and strategic planning. An index is also given.
Electronic reproduction.
Keywords: Business networks; Business communication; Employees; Incentives in industry; Strategic planning; Teams in the workplace; Electronic books